A new measurement method for the optical feedback coupling factor and linewidth enhancement factor based on self-mixing interferometry. (November 2022) - Zhao, Yunkun; Liu, Keyan; Ren, Guoyang; Du, Zhengting; Yu, Qi; Li, Hongtao; Tu, Guojie; Xu, Feng; Hu, Zhijia; Lu, Liang
Highlights: A new method is proposed to measure C and α -factor based on the self-mixing effect. Parameter C and α are obtained by tracking LETA area of the jumping points. This scheme has the optimum theoretical change sensitivity compared to other methods. The measured C in in the range of 1.0-4.5, and α -factor is evaluated as 2.41±0.146. Abstract: In this study, a practical and straightforward method is presented for measuring the optical feedback coefficient C and the linewidth enhancement factor α by means of the mode-hopping phenomena in the self-mixing interferometric system. A theoretical analytical model, in combination with the laser energy transition area of the phase jumping points and the C -parameter, is described deeply. In the experiment, a laser self-mixing vibration sensing system is fabricated to further verify this proposed theoretical model and simultaneously obtain the geometric area S R, F under different C values. From the actual measurements, the C -parameter is exactly measured by tracking the change of the geometric area S R, F, over the range of 1.0-4.5. Then, the α -factor of this self-mixing sensor is obtained as 2.41±0.15 with an accuracy of 6%. In addition, the absolute and relative error of the experimental results are less than 0.14 and 7.43%, respectively. In a word, the measured results agree well with the simulated values, of which validates the good applicability and practicability of this measurement method.